Tun Dr Mahathir Mohamad’s Early Efforts to Eemolish Dato’ Sri Mohd Najib Razak as a Prime Minister - Mohamed, Nik Mawardi; Yusoff, Kamarul Zaman; Omar, Rusdi (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2018)
The defeat of the Barisan Nasional (BN) Party in the hands of Pakatan Harapan (PH) Party in the 14th General Election (GE 14) Malaysia shocked many parties, both BN leaders and their own PH or political observers. This is because of the 3M factor, which is machinery, money and media, owned by BN, a split factor in the opposition pact that led to a three-cornered fight between BN, PH and Gagasan Sejahtera (GH) seen dominated by the Democratic Action Party (DAP) to create a perception that it has no Malay and Islamic agenda. It acknowledges that the three factors are the reasons why BN leaders and politics observers expect BN to be able to defend their win in GE 14 despite BN's chairman Dato’ Sri Mohd Najib Razak being swept away by 1Malaysia Development Berhad (1MDB). However, the opposition pact's opposition soon changed when former Prime Minister Tun Dr Mahathir Mohamad left United Malays National Organization Party (UMNO) to set up a new Malay party called Pribumi Bersatu Malaysia (BERSATU) Party, bringing BERSATU to PH, and even appointed as chairman of PH and the Prime Minister. This study saw the initial efforts used by Dr Mahathir to overthrow Najib and why this initial attempt failed to push Dr Mahathir out of UMNO to establish BERSATU and led him to PH